A study of peripartum cardiomyopathy in a tertiary care center in India - Joshi, Aditi V.; Fonseca, Michelle N.; Kharat-Kapote, Deepali S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Peripartum cardiomyopathy is an idiopathic and reversible form of dilated cardiomyopathy. The aim of the study was to study the mean age of presentation of peripartum cardiomyopathy in pregnant patients over a period of 1 year in a tertiary health care and study the maternal and fetal outcome of patients with peripartum cardiomyopathy. Methods: A retrospective observational study with total of 22 patients with peripartum cardiomyopathy was diagnosed in a total of 10,279 deliveries conducted at LTMMC, Sion hospital between September 2014 to February 2016. Results: Our study revealed that most of the affected patients were young with the mean age at presentation being 26.8±4.29 years. Most of the patients were diagnosed in the postpartum period (63.6%). the most common risk factor was pre-eclampsia (22.7%) followed by anemia (18.2%). The mean Ejection fraction at the time of presentation was 25.3±9.8%. There were 2 (9.1%) intrauterine fetal deaths and 1 neonatal death. Conclusions: There is a need for more multi-centric studies in order to understand the underlying pathogenesis and to determine the possible early interventions to help provide better pregnancy outcome.